2014
DOI: 10.1007/s11340-014-9947-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Knee Brace Migration and Associated Skin Deformation During Flexion by Full-Field Measurements

Abstract: Fabric-based knee braces are widely used as orthotic devices to support and align the joint. Despite significant prescription, compliance with the treatment is often negatively affected by discomfort issues, in particular brace slippage and migration. Full-field measurements associated with digital image correlation were performed on 11 subjects to determine if the brace was able to follow skin deformation during knee flexion, which was suspected to be a primary slippage mechanism. This technique allowed measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Another effect that causes misalignment and leads to discomfort issues is brace slippage. 21 A study by Brownstein 22 found a maximal migration of 11 mm after only 15 min of exercises. The misalignment of the rotation axes of knee and brace caused by the different kinematics and through brace slippage might influence structures within the knee.…”
mentioning
confidence: 98%
“…Another effect that causes misalignment and leads to discomfort issues is brace slippage. 21 A study by Brownstein 22 found a maximal migration of 11 mm after only 15 min of exercises. The misalignment of the rotation axes of knee and brace caused by the different kinematics and through brace slippage might influence structures within the knee.…”
mentioning
confidence: 98%
“…High interaction forces may result in skin sores, additional pain, or injuries (Chen et al, 2016 ; Gorgey, 2018 ). Studies such as Pierrat et al ( 2015 ); Anil Kumar et al ( 2019 ); Serrancoli et al ( 2019 ) have shown that interaction forces are strongly related to safety, comfort, and quality of walking with lower limb orthotics/exoskeletons.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is of great importance to have measurements of pressure and deformation fields all around the trunk. Full-field measuring techniques have attracted interest in many biomechanical studies, among them, pressure fields on feet [30] or buttocks [31] or strain fields on knee braces [32] or on the calf [33] but, to our knowledge, no direct application on lumbar belts exists. Moreover, it seems that no simultaneous pressure and strain field measurement on a compression device has been reported.…”
Section: Introductionmentioning
confidence: 99%